2016
DOI: 10.1007/s00192-016-2975-y
|View full text |Cite
|
Sign up to set email alerts
|

Voiding trial outcome following pelvic floor repair without incontinence procedures

Abstract: Introduction and hypothesis Our aim was to identify predictors of postoperative voiding trial failure among patients who had a pelvic floor repair without a concurrent incontinence procedure in order to identify low-risk patients in whom postoperative voiding trials may be modified. Methods We conducted a retrospective cohort study of women who underwent pelvic floor repair without concurrent incontinence procedures at two institutions from 1 November 2011 through 13 October 2013 after abstracting demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…Previous studies have shown that lower BMI, older women and anterior colporrhaphy are associated with higher risk of POUR [8][9][10][11][12]. In our analysis we found only modest differences in the reconstructive vs. obliterative approaches.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have shown that lower BMI, older women and anterior colporrhaphy are associated with higher risk of POUR [8][9][10][11][12]. In our analysis we found only modest differences in the reconstructive vs. obliterative approaches.…”
Section: Discussioncontrasting
confidence: 54%
“…Small peripheral nerve endings required for bladder sensation can become temporarily disrupted, resulting in a transient neuropathy and resultant bladder dysfunction [4]. Previously evaluated risk factors for POUR include: lower body mass index (BMI), advanced age, higher stage of prolapse, anterior colporrhaphy, previous incontinence surgery, and high preoperative post void residuals (PVR) [8][9][10][11][12]. Intravenous uid administration of >750mL or a bladder volume of > 270mL in the postanaesthetic recovery area has also been shown to increase the risk of POUR [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lower BMI, older women and anterior colporrhaphy are associated with higher risk of POUR [ 8 12 ]. In our analysis we found only modest differences in the reconstructive vs. obliterative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Small peripheral nerve endings required for bladder sensation can become temporarily disrupted, resulting in a transient neuropathy and resultant bladder dysfunction [ 4 ]. Previously evaluated risk factors for POUR include: lower body mass index (BMI), advanced age, higher stage of prolapse, anterior colporrhaphy, previous incontinence surgery, and high preoperative post void residuals (PVR) [ 8 12 ]. Intravenous fluid administration of > 750 mL or a bladder volume of ≥ 270 mL in the postanaesthetic recovery area has also been shown to increase the risk of POUR [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 They can help increase the detection of transient postoperative voiding dysfunction when compared to the traditional practice of monitoring for spontaneous voiding. However, evidence indicates that the risk of postoperative voiding dysfunction varies from 2% to 43% depending on the type of pelvic procedure 2,4,812 and there is still no consensus on the routine use of voiding trials following pelvic surgeries.…”
Section: Introductionmentioning
confidence: 99%